2001
DOI: 10.1152/jappl.2001.90.6.2203
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of slow and fast gastrocnemius muscle fibers after a 17-day spaceflight

Abstract: The purpose of this investigation was to study the effects of a 17-day spaceflight on the contractile properties of individual fast- and slow-twitch fibers isolated from biopsies of the fast-twitch gastrocnemius muscle of four male astronauts. Single chemically skinned fibers were studied during maximal Ca2+-activated contractions with fiber myosin heavy chain (MHC) isoform expression subsequently determined by SDS gel electrophoresis. Spaceflight had no significant effect on the mean diameter or specific forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
71
2
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 33 publications
8
71
2
3
Order By: Relevance
“…Decreases in muscle activity due to spaceflight 1) , unloading 2) and fixation of joints 3) often cause skeletal muscle atrophy. This is associated with a loss of contractile protein content due to decreases in overall protein synthesis 4) and increases in proteolysis 5) .…”
Section: Introductionmentioning
confidence: 99%
“…Decreases in muscle activity due to spaceflight 1) , unloading 2) and fixation of joints 3) often cause skeletal muscle atrophy. This is associated with a loss of contractile protein content due to decreases in overall protein synthesis 4) and increases in proteolysis 5) .…”
Section: Introductionmentioning
confidence: 99%
“…Human studies involving 17 days of bed rest (27,28) or spaceflight (26) revealed that maximal single fiber force (P 0 ) from the soleus muscle was decreased, mainly as a result of a decline in fiber cross-sectional area (CSA), and that maximal unloaded shortening velocity (V 0 ) was increased. Consequently, single fiber power was either maintained or depressed, depending on the study participant or fiber type (29), with fibers expressing type I MHC being generally more affected. Muscle unloading up to 4 mo in a long-term bed-rest study induced a similar pattern of adaptation in the functional properties of type I fibers from the soleus muscle (31), with changes seemingly proportional to the duration of unloading.…”
mentioning
confidence: 99%
“…Lately, it was reported that there is a differential turnover of myosin heavy chain (MyHC) proteins during muscle wasting [25][26][27][28][29]. Then, mobilization of gatrocnemius and soleus was established in the present study, wherein distinctive VEGFR2 trafficking was evoked.…”
Section: Discussionmentioning
confidence: 69%
“…Also, motor endplates on fast and slow muscle fibers show distinct transmitter release characteristics [25]. Accumulating evidence indicated that the degree of muscle denervation depends on muscle type, with atrophy more prominent in type I than in type II muscle fibers [26][27][28][29]. There is also a differential turnover of MyHC proteins during muscle wasting after a bed-rest period, which is indicative of muscle fibers in a transitional state [30].…”
Section: Introductionmentioning
confidence: 99%